Serology of Neisseria gonorrhoeae: W-antigen serogrouping by coagglutination and protein I serotyping by enzyme-linked immunosorbent assay both detect protein I antigens. - Sandstrom, E G (1982)
A total of 224 strains were serogrouped by coagglutination (COA) and serotyped by protein I enzyme-linked immunosorbent assay (ELISA). Of these strains, 61 were from patients with disseminated gonococcal infection, 21 were from patients with pelvic inflammatory disease, and 115 were from patients with uncomplicated gonococcal infection in Singapore, the Philippines, and Denmark. Twenty-seven were laboratory reference strains. Of the patient strains, 102 belonged to COA serogroup WI, and all of the 100 strains that typed with protein I serotypes 1, 2, or 3 were in this group. Most of the strains of gonococci from the 61 patients with disseminated gonococcal infection were within this group (COA WI, 53 or 87%; protein I serotypes 1, 2, or 3, 51 or 84%). All 46 strains that were protein I serotypes 4 through 7 were also COA serogroup WII. Protein I serotypes 8 and 9 accounted for 49 (25%) of the 197 patient strains. Twenty-eight of these strains typed as COA serogroup WII, 20 typed as serogroup WIII, and 1 typed as serogroups WII and WIII. COA W serogrouping and protein I ELISA both appeared to detect antigens on the protein I molecule of the outer membrane of Neisseria gonorrhoeae. Protein I serotyping, which uses unboiled organisms, may generally recognize more variable and surface-exposed antigenic determinants. In contrast, COA W serogrouping, which uses boiled organisms, may recognize less exposed shared antigenic determinants in addition to variable protein I antigenic determinants. Both methods may prove useful for further studies of the epidemiology and pathogenesis of gonorrhea.